Key components of the Polish position in regard to the Eastern policy of the European Union (Economic and Political Thought, 2015)
As early as in the period before the enlargement of the European Unionin 2004, Poland – as a candidate state at the time – took part in the debatebefore the European Neighbourhood Policy (formally introduced just a fewdays after the 2004 enlargement) was conceived. During the debate, thekey issue was the idea of further enlargement of the EU after adequaterequirements are met. One of the most important elements of the Polishprogramme within the EU Eastern policy in the period 2006–2014 wasenergy and activities within the Eastern Partnership. After Sweden supportedthe Eastern Partnership at its initial stage, Poland gained a lot of positiveexperience. A supposed permanent element of the Polish strategy withinthe EU Eastern policy was also its consent for the strengthening of commonEU institutions, especially in the internal policy, which might have beeninterpreted as promoting the principle of ‘more enlargement for deepening’for the co-operation within the EU. It can be perceived as an element oftransaction with the member states that were against or sceptical aboutenlargement and/or an attempt to strengthen Polish stand within the EUEastern policy with the use of common institutions. A specific canon of thePolish stand within the EU Eastern policy related to the Polish politicalthought tradition which has developed over the last 15 years. From the pointof view of the catalogue of Polish targets, one can notice a tendency in theEU to accept some Polish arguments as common ones – it is seen when thedevelopment of the idea and implementation of the ENP is compared withwhat resulted from the Eastern Partnership.